Párduc, oroszlán, gorilla? Afrika médiareprezentációja a vezető magyar hírportálok tükrében - Béni, Alexandra (Afrika Tanulmányok / Hungarian Journal of African Studies, 2020)
The article investigates how the most popular Hungarian news websites represent Africa in order to highlight the tendencies and patterns used in their communication. It is hypothesized that Hungarian news websites operate with negative images when covering issues related to Africa due to the fact that news outlets tend to rely on foreign news sources, which – according to the available literature – mainly broadcast in a generalising and unfavourable manner. The content and sentiment analysis of news units led to the conclusion that even though the analysed Hungarian news websites do not solely use negative images – some topics, such as “Science and technology” and “Hungarian-African relations”, have a markedly positive tone to them – the online media representation of Africa is more negative in general.